2020
DOI: 10.1137/19m124397x
|View full text |Cite
|
Sign up to set email alerts
|

Almost Envy-Freeness with General Valuations

Abstract: The goal of fair division is to distribute resources among competing players in a "fair" way. Envy-freeness is the most extensively studied fairness notion in fair division. Envy-free allocations do not always exist with indivisible goods, motivating the study of relaxed versions of envy-freeness. We study the envy-freeness up to any good (EFX) property, which states that no player prefers the bundle of another player following the removal of any single good, and prove the first general results about this prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
257
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(263 citation statements)
references
References 28 publications
(82 reference statements)
6
257
0
Order By: Relevance
“…We employ the natural and practical operation of donating/removing items to resolve the challenging issues related to the EFX solution concept. Our approach contrasts with the recent attempts to mitigate such challenges by considering approximate versions of EFX (e.g., in the papers by Plaut and Roughgarden [33] and Amanatidis et al [1]). Instead, we keep the precise definition of EFX and use approximation only for the efficiency guarantee which is unavoidable.…”
Section: Donation Of Itemsmentioning
confidence: 94%
See 1 more Smart Citation
“…We employ the natural and practical operation of donating/removing items to resolve the challenging issues related to the EFX solution concept. Our approach contrasts with the recent attempts to mitigate such challenges by considering approximate versions of EFX (e.g., in the papers by Plaut and Roughgarden [33] and Amanatidis et al [1]). Instead, we keep the precise definition of EFX and use approximation only for the efficiency guarantee which is unavoidable.…”
Section: Donation Of Itemsmentioning
confidence: 94%
“…Unlike EF1, the existence of EFX allocations is still a mystery, even for three agents with additive valuations. Plaut and Roughgarden [33] prove the existence of EFX allocations for setting with two agents only or with more agents and identical valuations. In addition, they present an algorithm for computing an 1/2-EFX allocation, where the value of each agent from her bundle is at least half of what the EFX property requires it to be.…”
Section: Related Workmentioning
confidence: 99%
“…These relaxations include envy-freeness up to one good-any envy that an agent has towards another agent can be eliminated by removing some item from the latter agent's bundle-and envy-freeness up to any goodany such envy can be eliminated by removing any item from the latter agent's bundle. It has been shown that these relaxations do provide existence guarantees in a number of settings (Lipton et al, 2004;Caragiannis et al, 2016;Biswas and Barman, 2018;Plaut and Roughgarden, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…If the above requirement of submodularity is replaced by strictly increasing subadditivity, an MMAX allocation is guaranteed to exist. In contrast, MMS allocation may not exist even for three agents with additive valuations [Kurokawa et al, 2018] and an EFX allocation is only known to exist when there are two agents [Plaut and Roughgarden, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…In [Caragiannis et al, 2016], the authors introduced a strictly stronger fairness notation than EF1 called envy-free up to any good (EFX), where the comparison is made to "any" single good instead of "a" single good. The state-of-the-art results show that an EFX allocation exists in the following settings: (1) there are 2 agents, or (2) there are any number of agents but all of them have the identical valuation [Plaut and Roughgarden, 2018]. It is still an open question whether an EFX allocation exists in general, even for additive valuations.…”
Section: Introductionmentioning
confidence: 99%